2001
DOI: 10.1002/joc.600
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation seasonality in eastern and southern coastal Spain

Abstract: The nature of the seasonality of precipitation in eastern and southern coastal Spain (including both the Mediterranean and the far southwestern Atlantic provinces) is examined using monthly precipitation values available for 410 sites for the period 1964-1993. Important contrasts are illustrated between eastern (Mediterranean) and southern (Atlantic) areas. In the east, seasonality is more subdued due to incursions of fronts from the north at all times of the year. In the far south, the months of July and Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 15 publications
5
100
0
8
Order By: Relevance
“…the westerly circulation types) and Mediterranean (i.e. the easterly circulation types) influences, are supported by an extensive literature (Linés Escardó, 1970;Corte-Real et al, 1995Rodó et al, 1997;Zhang et al, 1997;Goodess and Palutikof, 1998;Esteban-Parra et al, 1998;Rodriguez-Puebla et al, 1998;Romero et al, 1998Romero et al, , 1999aMartin-Vide and Gomez, 1999;Serrano et al, 1999;Estrela et al, 2000;Goodess, 2000;Spellman, 2000;Trigo and DaCamara, 2000;Sumner et al, 2001).…”
Section: Circulation Typesmentioning
confidence: 73%
See 2 more Smart Citations
“…the westerly circulation types) and Mediterranean (i.e. the easterly circulation types) influences, are supported by an extensive literature (Linés Escardó, 1970;Corte-Real et al, 1995Rodó et al, 1997;Zhang et al, 1997;Goodess and Palutikof, 1998;Esteban-Parra et al, 1998;Rodriguez-Puebla et al, 1998;Romero et al, 1998Romero et al, , 1999aMartin-Vide and Gomez, 1999;Serrano et al, 1999;Estrela et al, 2000;Goodess, 2000;Spellman, 2000;Trigo and DaCamara, 2000;Sumner et al, 2001).…”
Section: Circulation Typesmentioning
confidence: 73%
“…-Portugal (Corte-Real et al, 1995;Zhang et al, 1997;Trigo and DaCamara, 2000) -the Spanish Mediterranean coastal region (Romero et al, 1998(Romero et al, , 1999aSumner et al, 2001) -the Valencia region (Estrela et al, 2000;Egozcue and Ramis, 2001;González-Hidalgo et al, 2001). …”
Section: Aims Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of this heterogeneity, annual trends are characterized globally by a general decrease in precipitation (−12%), with increased variability to the south of the Gulf of Valencia, but a decrease in the north in the period 1951-2000. Sumner et al (2001) suggested that socioeconomic problems require a detailed analysis of precipitation in these areas of Spain, which is true, as since 1950, the population has grown by 86.2% over the study area as a whole, with growth in the coastal provinces rising to 107.3%, but only to 27.6% inland. Furthermore, the inland population is mainly concentrated in a small number of towns and the rural exodus continued up to the early 1980s, particularly in mountain areas.…”
Section: Discussionmentioning
confidence: 99%
“…A wider geographical scale that includes the Catalan territory has been adopted by different workers in their research on the annual, seasonal and monthly rainfall regime of the Iberian Peninsula, by means of principal component (PC) techniques (Fernández-Mills, 1995;Esteban-Parra et al, 1998;Rodríguez-Puebla et al, 1998;Serrano et al, 1999;García et al, 2002) and of the Spanish Mediterranean area (Romero et al, 1998(Romero et al, , 1999aSumner et al, 2001). In all the aforementioned cases, daily data were used to obtain monthly, seasonal and annual amounts, which constituted the database for these studies.…”
Section: E D I T E R R a N E A N S Ementioning
confidence: 99%